NHM Industries: Ups and Downs of SMEs Business Venture - Fakhrul Anwar, Zainol; Nalini, Arumugam; Nor Asmahani, Ibrahim; Wan Norhayate, Wan Daud (2014)
NHM Industries (NHM) is an established small medium enterprises (SMEs) owned by two siblings which operated since 1996 in Kuala Terengganu, Terengganu, Malaysia. The biggest achievement of NHM is the company able to achieve the sales around 5 million in year 2003 and 2004. However, it was a short success, the company‟s sales decline drastically from 2006 till 2013. Even though the vision of NHM is to be the leading service providers, contractors and suppliers in the land and marine electrical and electronic systems which is offered on land, sea and the oil and gas companies, however the company‟s achievement is still far to reach the expected vision. Many challenges and issues in operation and management must be encountered by NHM. This case study will look at the operational challenges and several issues faced by NHM, internally and externally.